Analysis of long-term results of Metrogil vaginal gel and Metrogil plus in the treatment of recurrent vaginal biocenosis disorders - T. V. Provotorova (Акушерство, гинекология и репродукция, 2018)
Aim: to study the efficacy of Metrogil vaginal gel and Metrogil plus in patients with recurrent vaginal biocenosis disorders. Materials and methods. A total of 234 patients were examined. Among them, 115 women with mixed flora without Candida spp in their vaginal microbiome, received Metrogil vaginal gel treatment (group 1), and 119 women with mixed flora and Candida spp. in their vaginal microbiome, received treatment with Metrogil plus applied as an intravaginal gel (group 2). To assess the treatment efficacy, patients’ complaints, objective examination data, pH-metry, smear microscopy, and polymerase chain reaction (PCR) results were analyzed. Results. In the vaginal microbiome of all patients before treatment, the presence of heterogeneous gram-positive and gram-negative flora was detected; among those bacteria, a markedly decreased presence of Lactobacillus spp. (to 102-103 cfu/ml) and a dramatically increased presence of Gardnerella vaginalis, Atopobium vaginae, Mobiluncus spp. was found; there was also a significant amount of Candida spp. in patients of group 2. By the end of the treatment, the patients presented no complaints, there were no objective clinical symptoms, the pH values came to normal, and the PCR results showed an improvement in the qualitative and quantitative composition of the vaginal microflora. In most patients, this positive result persisted for 3 months. Conclusion. The decision on pharmacotherapy in patients with recurrent disbalance of vaginal biocenosis should be based on the qualitative composition of the vaginal microbiome.